2016
DOI: 10.1083/jcb.201504137
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the actin cytoskeleton mediates receptor cross talk: An emerging concept in tuning receptor signaling

Abstract: Recent evidence implicates the actin cytoskeleton in the control of receptor signaling. This may be of particular importance in the context of immune receptors, such as the B cell receptor, where dysregulated signaling can result in autoimmunity and malignancy. Here, we discuss the role of the actin cytoskeleton in controlling receptor compartmentalization, dynamics, and clustering as a means to regulate receptor signaling through controlling the interactions with protein partners. We propose that the actin cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 149 publications
6
102
0
Order By: Relevance
“…have made it possible to observe the detailed organization of actin filaments in B cells and begin to unravel the mechanisms by which cytoskeletal defects affect individual signalling pathways 9 . The emerging picture is that the cytoskeleton provides structural and energy-dependent regulation of biochemical reactions in the cell.…”
Section: Recent Advances In Cellular Imaging (Box 1) and Biophysical mentioning
confidence: 99%
See 2 more Smart Citations
“…have made it possible to observe the detailed organization of actin filaments in B cells and begin to unravel the mechanisms by which cytoskeletal defects affect individual signalling pathways 9 . The emerging picture is that the cytoskeleton provides structural and energy-dependent regulation of biochemical reactions in the cell.…”
Section: Recent Advances In Cellular Imaging (Box 1) and Biophysical mentioning
confidence: 99%
“…Both in the absence and presence of antigen, BCR signalling operates in a continuous balance between kinase and phosphatase reactions. Pharmacological and genetic manipulations show that this balance is maintained by the cortical cytoskeleton 9 , suggesting that actin regulates the access of membrane kinases and phosphatases to their substrates. These effects can be explained by several distinct mechanisms involving the influence of cortical actin on the diffusion of membrane proteins 88 .…”
Section: [H1] Cytoskeletal Regulation Of Bcr Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…This organization is mediated by lipid-lipid, lipid-protein and proteinprotein interactions within the membrane (Simons and Gerl, 2010), and by membrane-cortical-cytoskeleton interactions (Jaqaman and Grinstein, 2012;Mattila et al, 2016;Morone et al, 2006). Much remains to be determined about the nature of nanoclustering, the mechanisms leading to it and its consequences for receptor signaling (Garcia-Parajo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Integrin signaling is a pathway that controls rearrangement of the actin cytoskeleton (24). It has been suggested that the actin cytoskeleton may regulate receptor signaling, which is particularly important for the B-cell receptor and dysregulated signaling may result in autoimmunity and malignancy (25).…”
Section: Discussionmentioning
confidence: 99%